Emerging Trends on the Implementation of Nanomaterials for Improving the Performance of Photovoltaic Thermal Systems: Energetic, Exergetic, Environmental, and Economic Perspectives. Issue 12 (5th November 2021) - Tyagi, Praveen Kumar; Kumar, Rajan
Abstract : This study presents an updated and constructive review that explores the impact of nanomaterials on the photovoltaic thermal (PVT) system performance from energy, exergy, environmental, and economic perspectives. The study employs the various PVT configurations using water, ethylene glycol, nanofluid, phase change material, and nanoenhanced phase change material, as well as a combination of these cooling media at different loadings, to overcome the increased photovoltaic (PV) module temperature levels in the presence of nanomaterials and improve both the cooling and thermal regulation of the PVT systems. The average PV module temperature, temperature gain across the working fluid, thermal, electrical, and overall energetic and exergetic efficiencies, exergy loss, payback period, cost of energy, and CO2 mitigation/year are some of the primary metrics used to evaluate the performance of PVT systems. The study concludes that the use of nanomaterial in PVT systems enhances the energetic and exergetic performance and these systems are effective in decreasing the entropy generation and exergy loss because of their improved heat transfer. The present study also concludes that payback time and cost of energy for the nanomaterial‐based PVT system are lower than that of conventional systems and these systems prevent greenhouse gases emissions in the ecosystem. Abstract : This study presents an updated review exploring the impact of nanomaterials on the photovoltaic thermal (PVT) system performance from energy, exergy, environmental, and economic perspectives. The review article also highlights the future research directions in this thrust area. It is hoped that this review will help to improve the performance of nanomaterial‐based PVT systems from the aforementioned perspectives.